Temporary Anchorage Devices in Combined Treatments: Bridging Orthodontics and Prosthetics - Nastarin , Parastou; Sharifi , Reza; Hosenzadegan, Mortaza; Gharouni , Mahya; Habibkhodaei, Maliheh (Galen Medical Journal, 2024)
Temporary Anchorage Devices (TADs) have become a cornerstone in modern orthodontics and prosthetic dentistry, offering reliable skeletal anchorage that enhances treatment precision and flexibility. This review explores the application of TADs in combined orthodontic-prosthetic treatments, emphasizing their growing significance in interdisciplinary care. This review aims to assess the role of TADs in addressing complex treatments that involve both orthodontic tooth movement and prosthetic restoration, while also examining their clinical effectiveness, treatment protocols, and anticipated innovations. TADs have revolutionized orthodontic treatments by providing stable anchorage for space closure, distalization, and intrusion, which would otherwise be challenging with traditional methods. They are increasingly utilized in prosthetic dentistry, particularly in cases involving edentulous spaces or insufficient bone support, where they provide temporary anchorage until permanent solutions, such as implants, can be placed. Several case studies demonstrate the effectiveness of TADs in aligning teeth and supporting prosthetic devices, highlighting their ability to streamline treatment and improve both functional and aesthetic outcomes. Technological advancements, such as 3D printing and digital planning tools, are improving the precision of TAD placement. Concurrently, innovations in biomaterials, like bioactive coatings, are enhancing osseointegration and reducing the risk of complications. As these technologies evolve, TADs are expected to become an integral part of fully digital treatment workflows, further improving outcomes in interdisciplinary cases. TADs serve as a critical tool in bridging orthodontics and prosthetics, providing enhanced control and versatility in complex treatments. Future research will likely focus on improving their design and expanding their applications, ensuring they remain a pivotal component of modern dental care.